American ethnic history : themes and perspectives - McDonald, Jason (Jason J.) (Edinburgh University Press, 2007)
This book offers a thematic introduction to American ethnic history which provides an overview of key historiographical debates. It provides a new framework for examining and comprehending the varied historical experiences of ethnic groups in the United States. Thematically organized and comparative in outlook, it explores how historians have grappled with questions that bear upon a key aspect of the American experience: ethnicity. How did the United States come to have such an ethnically diverse population? What contribution, if any, has this ethnic diversity made to the shaping of American culture and institutions? How easily and at what levels have ethnic and racial minorities been incorporated, if at all, into the social and economic structures of the United States? Has incorporation been a uniform process or has it varied from group to group? This is both an authoritative introduction to the field of American ethnic history and a valuable reference tool for secondary scholoars.